Effect of omega-6 linoleic acid on neurobehavioral development in Caenorhabditis elegans. (April 2023) - Chen, Tun-Chieh; Hsu, Wen-Li; Wu, Ching-Ying; Lai, Yun-Ru; Chao, How-Ran; Chen, Chu-Huang; Tsai, Ming-Hsien
Highlights: Supplementary omega-6 LA with low concentration in worms increases the lifespan and maintains healthy growth. Excess LA intake potentially causes more activity of serotonergic neurons and interrupts lifespan regulation via aggravated intracellular ROS accumulation. LA at daily intake from foods in infants and children has to be carefully administrated. Abstract: Linoleic acid (LA, omega-6), an essential polyunsaturated fatty acid, is supplied by vegetable oils such as corn, sunflower and soybean. Supplementary LA in infants and children is required for normal growth and brain development, but has also been reported to induce brain inflammation and neurodegenerative diseases. This controversial role of LA development requires further investigation. Our study utilized Caenorhabditis elegans ( C. elegans ) as a model to clarify the role of LA in regulating neurobehavioral development. A mere supplementary quantity of LA in C. elegans larval stage affected the worm's locomotive ability, intracellular ROS accumulation and lifespan. We found that more serotonergic neurons were activated by supplementing LA above 10 μM thereby promoting locomotive ability with upregulation of serotonin-related genes. Supplementation with LA above 10 μM also inhibited the expression of mtl-1, mtl-2 and ctl-3 to accelerate oxidative stress and attenuate lifespan in nematodes; however, enhancement of stress-related genes such as sod-1, sod-3, mtl-1, mtl-2 and cyp-35A2 by supplementary LA under 1 μM decreased oxidative stress and increased the worm's lifespan. In conclusion, our study reveals that supplementary LA possesses both pros and cons in worm physiology and provides new suggestions for LA intake administration in childhood.